2019
DOI: 10.1111/jog.14114
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of 25‐hydroxyvitamin D and obesity among early pregnant women

Abstract: Aim: To assess serum 25-hydroxyvitamin D 25(OH)D level in obese pregnant Sudanese women in early pregnancy. Methods: A match case-control study was conducted in Saad Abualila Hospital (Khartoum, Sudan). The cases were obese (body mass index [BMI] ≥ 30.0 kg/m 2 ) women. Controls were women with normal BMI (18.5-24.9 kg/m 2 ) matched for age, parity and gestational age. The 25(OH)D level was measured using ELISA.Results: There was no significant difference between the two groups in their age, parity or gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Results indicated a positive association between maternal serum 25(OH)D concentration and the number of parity. One study mentioned that there was no significant difference between serum 25(OH)D concentration and age, parity, or gestational age [ 35 ], and no association between parity and 25(OH)D concentration was observed in another study [ 36 ]. While Shen et al found that high parity was associated with increasing serum vitamin D status [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated a positive association between maternal serum 25(OH)D concentration and the number of parity. One study mentioned that there was no significant difference between serum 25(OH)D concentration and age, parity, or gestational age [ 35 ], and no association between parity and 25(OH)D concentration was observed in another study [ 36 ]. While Shen et al found that high parity was associated with increasing serum vitamin D status [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that there was a positive correlation between maternal serum VD level and the number of parity; women who had given birth 3 times had higher serum VD than those giving birth 2 or 1 time (s) (p=0.016 and 0.039, respectively, Table 5a and 5b) . One study mentioned that there was no signi cant difference between the serum VD level and age, parity, or gestational age [25]. The mechanism underlying this phenomenon is therefore unclear; there could be certain compensation in metabolism function during pregnancy that requires further investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was (60 women in each arm) calculated as the ratio of 1:1 between the cases and the controls. Depending on our previous reports on the serum concentration of 25(OH)D (15.0 ng/mL) among pregnant Sudanese women [23], we assumed that women with PB would have a concentration of 25(OH)D of 10.0 ng/mL. Based on our recent reports on the level of 25(OH)D among women with preeclampsia [24], we assumed a mean difference of 5 ng/mL in the serum 25(OH)D concentration between the women who had PB and the healthy controls.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…There are no published data on the association between serum 25(OH)D concentrations/vitamin D deficiency and risk of PB in Sudan. We recently reported that the majority (94%) of pregnant Sudanese women have vitamin D deficiency (≤20 ng/mL) [23]. Thus, it is vital to determine if vitamin D levels are associated with PB in Sudan.…”
Section: Introductionmentioning
confidence: 99%